Association between the quality of plant‐based diets and risk of frailty. Issue 6 (30th September 2022) - Sotos‐Prieto, Mercedes; Struijk, Ellen A.; Fung, Teresa T.; Rodríguez‐Artalejo, Fernando; Willett, Walter C.; Hu, Frank B.; Lopez‐Garcia, Esther
Abstract: Background: The Mediterranean diet and other dietary patterns rich in fruits and vegetables have been linked to lower risk of frailty in older adults. However, not all plant‐based diets are necessarily healthful, and no previous study has evaluated the role of the quality of plant‐based dietary patterns in frailty risk. Our aim was to assess the association between plant‐based diet quality and risk of frailty. Methods: Prospective cohort consisted with 82 234 women aged ≥60 years from the Nurses' Health Study, who were followed from 1990 through 2014. The dates of analysis were April 14 to June 23, 2021. Dietary data were collected every 4 years using a validated semi‐quantitative food frequency questionnaire. The plant‐based diet quality was assessed with two indices (range 18–90 points): (a) healthful plant‐based diet index (hPDI), where healthy plant foods (whole grains, fruits, vegetables, nuts, legumes, vegetable oils and tea/coffee) received positive scores, while less healthy plant foods (fruit juices, sweetened beverages, refined grains, potatoes, and sweets/desserts) and animal foods received reverse scores; and (b) unhealthful plant‐based diet index (uPDI) where positive scores were given to less healthy plant foods and reverse scores to healthy plant foods and animal foods. Frailty incidence was assessed every 4 years, being defined as having three or more of the following five criteria from the FRAIL scale: fatigue, low strength, reduced aerobic capacity, having ≥5 illnesses and weight loss ≥5%. Multivariable‐adjusted Cox proportional‐hazards models were used to estimate hazard ratios (HRs) and their 95% confidence interval (CI). Results: We identified 12 910 incident cases of frailty over 1 176 401 person‐year follow‐up. In the multivariable analysis, the hPDI was inversely associated with the risk of frailty (hazard ratio [HR] for the highest vs. lowest quintile: 0.77, 95% confidence interval: 0.72–0.81; P trend <0.001). In addition, a 10‐unit increment in the hPDI was associated with a relative 15% lower risk of frailty. Conversely, a direct association was found between the uPDI and risk of frailty (HR highest vs. lowest quintile: 1.24 [1.17, 1.32], P trend <0.001). These associations were consistent for each frailty criterion, among participants with no frailty criteria at baseline, after excluding participants with diabetes, cancer and cardiovascular disease at baseline, for alternative versions of the plant‐based diet indices (PDIs), in subgroup analysis by categories of potential confounders, and in latency analysis. Conclusions: A healthful plant‐based diet was associated with lower risk of frailty whereas an unhealthful plant‐based diet was associated with higher risk.